ANALISIS KONTRIBUSI PAJAK KENDARAAN BERMOTOR TERHADAP PENDAPATAN ASLI DAERAH PROVINSI SULAWESI UTARA PERIODE (2013-2017) - Assa, Pinkan Grace; Manossoh, Hendrik; Mawikere, Lidia (Universitas Sam Ratulangi, 2018)
Regional Tax is one component of Regional Original Income which has very good prospects to be developed. Motor vehicle tax is one source of income in the Province. Regional Vehicle Revenue Tax North Sulawesi Province (2013-2017) The method of analysis in this study is a qualitative descriptive analysis method, namely tax revenues, especially motor vehicles in the period (2013-2017) using the contribution ratio. The results of the study explain the small contribution given by motor vehicle tax, and there are still many people who have not been obedient in paying taxes.Keywords: Regional Tax, Motor Vehicle Tax, Contributions, Receipts, Regional Income